Structural and physical studies of PVC/PVDF doped Nano lithium salt for electrochemical applications - Abdelghany, A. M. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Polymer blend of poly (vinyl chloride) and poly(vinylidene fluoride) of nominal composition (30PVC/70PVDF) wt:wt were prepared in the form of thin films using casting technique. Samples of the same composition doped with gradient concentration of nano lithium salt (LTO) were prepared and studied. Proposed filler was characterized using Fourier transform infrared spectroscopy (FTIR), UV/vis. optical absorption, X-ray diffraction (XRD), Transmission electron microscopy (TEM) and Electron diffraction (ED).Â  Obtained data approve the crystalline nano structure of filler with a cubic structure of average size (25-30 nm). Prepared nano composites were then investigated using different spectroscopic methods. XRD reveals the amorphous nature of the base polymer blend with tendency for increase in crystallinity with increasing the content of lithium salt. FTIR shows a preservation of the main vibrational spectral bands in their position with small variation in the area and intensity of some spectral bands related to the interaction between polymer and filler.